1999
DOI: 10.1002/(sici)1097-0193(1999)8:4<170::aid-hbm2>3.3.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between ventral stream for object vision and dorsal stream for spatial vision: An fMRI+ERP study

Abstract: Recent imaging studies indicated the existence of two visual pathways in humans: a ventral stream for object and form vision and a dorsal stream for spatial and motion vision. The present study was motivated by a stimulating question: Supposing shape and motion are processed separately in the two pathways, how do the respective cortical areas respond to the stimuli of "forms defined by motion"? fMRI and ERP recordings were combined in order to measure the spatiotemporal activation pattern in the two pathways r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…In addition, it may correspond to the dynamic form pathway as postulated by Zeki (1993), for which area V3 has been proposed to be an important processing stage (Zeki, 1993;Gegenfurtner et al, 1997). Support for this notion comes from a study by Wang et al (1999), who demonstrated strong dipole sources in ventral areas in response to form-from-motion stimuli and much weaker dipole sources in response to pure motion stimuli, whereas dorsal dipole sources responded strongly to both.…”
Section: Disentangling Direction-dependent and -Independent Motion Prmentioning
confidence: 88%
See 4 more Smart Citations
“…In addition, it may correspond to the dynamic form pathway as postulated by Zeki (1993), for which area V3 has been proposed to be an important processing stage (Zeki, 1993;Gegenfurtner et al, 1997). Support for this notion comes from a study by Wang et al (1999), who demonstrated strong dipole sources in ventral areas in response to form-from-motion stimuli and much weaker dipole sources in response to pure motion stimuli, whereas dorsal dipole sources responded strongly to both.…”
Section: Disentangling Direction-dependent and -Independent Motion Prmentioning
confidence: 88%
“…translation vs. rotation) have recently been demonstrated (e.g. Wang et al. , 1999; Delon‐Martin et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations